Pengaruh Pendekatan TPACK Dan Motivasi Belajar Terhadap Penguasaan Konsep Materi Interaksi Sosial Siswa SD - Desiana, Yulia; Amprasto, Amprasto; Rumanta, Maman (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The goal of this study is to examine the impact of Technological Pedagogical Content Knowledge (TPACK) and motivational learning on the mastery of social interactions among fifth-grade students at Cilegon 4 Elementary School. The population for this study comprises 128 students, and a sample of 78 students was selected. This sample was divided into two experimental classes, each containing 39 students—one utilizing a video-based approach and the other employing a PowerPoint-based method. This study employs a 2x2 factorial design for research design.The data analysis for this study involved the utilization of two-way-ANOVA. The study's findings reveal a p-value of 0.000 (p < 0.05), with F calculated (3737.406) exceeding the critical F value (4.09). As a result, this indicates a statistically significant outcome. The study's conclusion underscores that the utilization of TPACK combined with motivational learning significantly influences the mastery of social interactions among fifth-grade students at Cilegon 4 Elementary School.